Open Data Government in The 2024 Election: Sirekap Application - Murniyati Yanur; Erinda Alfiani Fauzi; Andi Ilmi Utami Irwan (Journal Ilmu Sosial, Politik dan Pemerintahan, 2025)
Open data is the right of all people in all lines including in the implementation of the 2024 election. Open data in the implementation of the 2024 election is assisted by several applications and websites, one of which is SIREKAP. The SIREKAP application is used by the head and members of the KPPS to monitor and evaluate election data in 2024. This study uses a qualitative method with a descriptive approach. The results of this study are that the SIREKAP application has a full effect in supporting Open data during the 2024 Election, this is evidenced by the application in real time providing the information needed in the 2024 election process. The obstacles to SIREKAP are the limited technological infrastructure and internet connectivity in several areas, especially in Central Kalimantan, which can slow down the vote recapitulation process, so that the data delayed displayed to KPPS.